LITERATUR TAFSIR BI AL MATSUR DI KALANGAN SUNNI: Tinjauan Historis dan Metodologis - Hamdan, Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
This article aimed to map the literature of Quran exegesis prevailing for Sunni.There are seven literatures classified as a tafsir bi al matsur, and four of themelaborated as comparison, namely Adhwa al Bayan fi Iydhah al Quran bi alQuran of asy Syinqithi, Jami al Bayan fi Tawil al Quran of Ibnu Jarir alThabari, Tafsir al Quran al Adzhim of Ibnu Katsir and al Dar al Mantsur fiat Tafsir bi al Matsur of Imam Suyuthi. The historical study and methodologyare the main subject of this literatures research using library approach. Theresearch show that there are some excellence and weakness of each literatures ifthey are viewed by methodology aspect. But according definition of al Matsur,the most valid (mutamad) literature is Adhwa al Bayan fi Iydhah al Quran bial Quran. Whereas according to turats and seniority of writer, the most validliterature is Jami al Bayan fi Tawil al Quran. The third position is Tafsir alQuran al Adzhim, as a resume of Jami al Bayan fi Tawil al Quran. And thelast position is al Dar al Mantsur fi at Tafsir bi al Matsur, because its sanadvalidation only pin up the closest of rawi.